Proses Naturalisasi Warga Negara Asing menjadi Warga Negara Indonesia Menurut Undang Undang 12 Tahun 2006 tentang Kewarganegaraan - Andhika Dimaz Pratama Angi; Josef Mario Monteiro; Megi Octaviana Radji (Student Scientific Creativity Journal, 2026)
Citizenship issues, particularly the naturalization of foreign nationals, remain an important challenge in Indonesia’s legal system. This study analyzes the implementation of the naturalization process under Law Number 12 of 2006 on the Citizenship of the Republic of Indonesia and identifies factors that hinder its implementation in East Nusa Tenggara Province. The research employed a normative legal method supported by empirical data using statutory, conceptual, and socio-legal approaches. Data were collected through a literature review and interviews with officials of the Regional Office of the Ministry of Law and Human Rights of East Nusa Tenggara and naturalization applicants. The findings show that the naturalization process has generally been carried out in accordance with applicable legal provisions, including application submission, administrative and substantive examination, government approval, and the citizenship oath. However, implementation remains constrained by incomplete documents, identity discrepancies, limited Indonesian language proficiency, inadequate understanding of procedures, restricted technological access in remote areas, lengthy administrative verification, and delays in renouncing original citizenship. The study concludes that effective naturalization depends not only on legal regulations but also on efficient administrative services, inter-agency coordination, and public legal awareness to ensure greater legal certainty.